The story of South African English:A brief linguistic overview - Bekker, Ian (International Journal of Language, Translation and Intercultural Communication, 2012)
This article provides a linguistic overview of the history and current status of South African English (SAfE). With respect to the history of this variety it deals with its colonial origins, subsequent development as well as diversifi cation into a number of sub-varieties, both L1 and L2 in nature. Next, the article provides a brief synchronic overview of the dialect-specifi c features of this variety, focusing mainly on phonetics and phonology, but also dealing with morphology, lexis and grammar where pertinent. The last section of the article focuses on recent developments, both in terms of the variety itself and research in the field.